Tourism and Geocities: Geographical Implications - Graziella FERRARA (Editura Universităţii din Oradea, 2016)
This study analyzed geographical implications of first race of 34th America's Cup on Naples. According to our results, America's Cup contributed to create a positive image of Naples as touristic destination. Results of this study indicated that both male and famale enjoied American's Cup in Naples. These results can be used by policy-makers in planning future turistic events in Naples.